Kadar Protein Dan Sifat Organoleptik Es Krim Tape Sukun Dengan Penambahan Sari Kacang Kedelai Dan Ubi Ungu Sebagai Pewarna Alami - SAFITRI, Ita; , Dra. Aminah Asngad, M.Si (2015)
Ice cream is a solid food made from milk combined with flavorings, sweeteners and other frozen foods. In this study the manufacture of ice cream using a mixture of cow's milk, soy bean extract, tape breadfruit and purple potato extract. This study aims to determine the levels of soluble protein, speed and organoleptic melted ice cream tape breadfruit with the addition of soy bean extract and purple potato extract. Levels of soluble protein in the ice cream was measured by using the method lowry. Research design using a completely randomized design 2 factor. Factor 1 : soy bean extract comparison with cow's milk K0 : 0:100%, K1 : 40:60%, K2 : 50:50%. Factor 2 : purple potato extract concentration P1 : 30%, P2 : 40%, P3 : 50% with 3 repetitions. The highest protein content in treatment K2P2 (soy bean extract 50%, cow's milk 50%, breadfruit tape 20%, purplr potato extract 40%) as much 1,105%, treatment K1P1 (Soy bean extract 40%, cow's milk 60%, breadfruit tape 20%, purple potato extract 30%) has a melt speed for 12 minutes, and organoleptic treatment K1P3 (Soy bean extract 40%, cow's milk 60%, breadfruit tape 20%, purple potato extract 50%) an ice cream products are the most dominant perple, distinctive odor tape, sweet taste, soft texture, and acceptance of their panelist like. Based on research result of high levels of protein, melt velocity, and organoleptic, influenced by the addition soy bean extract and purple yam ice cream.